Dynamics of the European sovereign bonds and the identification of crisis periods - Zhenxi Chen; Stefan Reitz (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
We develop an empirical model of heterogeneous agents to study the dynamics of the European sovereign bonds market. Agents make use of different information from the CDS market and the historical price movements of the sovereign bonds for their trading decisions. Subject to the perceived risk, agents exhibit changing trading behaviors in high risk periods and tranquil times. As a robustness check for the ability of our model to identify crises periods we also run a generalized sup adf test as suggested in Phillips, Shi, and Yu (2015) . Our results indicate that the smooth transition regression framework may provide additional valuable information regarding the timing of crisis events.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C32; C5; G15; 330; sovereign bonds; CDS; heterogeneous agents